2019
DOI: 10.1080/21645515.2018.1558688
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent providers’ knowledge of human papillomavirus vaccination age guidelines in five countries

Abstract: Purpose: To examine provider knowledge of HPV vaccination age guidelines in five countries. Methods: A total of 151 providers of adolescent vaccinations in Argentina, Malaysia, South Africa, South Korea, and Spain were interviewed between October 2013 and April 2014. Univariate analyses compared providers' understanding of recommended age groups for HPV vaccination to that of each country's national guidelines. Results: In three of five countries surveyed, most providers (97% South Africa, 95% Argentina, 87% M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The knowledge of providers (parents or guardians) about the guidelines for HPV vaccination was evidenced in a study that a substantial proportion where providers incorrectly reported the target ages of their countries for HPV vaccination [15]. As the providers' recommendation is among the strongest predictors of successful vaccination among adolescents, better education and clarification of national guidelines for providers administering HPV vaccination are essential to optimize infection prevention and associated diseases [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The knowledge of providers (parents or guardians) about the guidelines for HPV vaccination was evidenced in a study that a substantial proportion where providers incorrectly reported the target ages of their countries for HPV vaccination [15]. As the providers' recommendation is among the strongest predictors of successful vaccination among adolescents, better education and clarification of national guidelines for providers administering HPV vaccination are essential to optimize infection prevention and associated diseases [15].…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of providers (parents or guardians) about the guidelines for HPV vaccination was evidenced in a study that a substantial proportion where providers incorrectly reported the target ages of their countries for HPV vaccination [15]. As the providers' recommendation is among the strongest predictors of successful vaccination among adolescents, better education and clarification of national guidelines for providers administering HPV vaccination are essential to optimize infection prevention and associated diseases [15]. Not only do providers have low knowledge about HPV, but it has been verified in a before-and-after clinical trial in order to assess the prior knowledge of medical students about HPV; the percentage of correct answers was 45.6% showing limited knowledge on the subject [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Other papers address provider, parent, and patient issues specific to understudied countries, such as China, India, and Italy, as well as areas of vaccine hesitancy and/or low vaccination uptake in the U.S. and Canada. [37][38][39][40][41][42][43][44] Another research report found that few providers in a U.S. regional health plan administered vaccine in a way that was consistent with Healthcare Effectiveness Data and Information Set benchmarks. 45 Two articles explore issues of trust among African American parents and how this impacts vaccination.…”
Section: Hpv Vaccination Policymentioning
confidence: 95%